Agent verification design of short text messaging system using formal method - Selamat, Ali (Elsevier, 2009)
Today, in the evolution of hardware and software system in mobile-driven applications, failure is unacceptable to many entrepreneurs. The use of Short Message Service (SMS) for internet-based business is acknowledged to be one of the applications that have a potential to give unreliable results to the information systems. Once the workload is optimized, the network traffic becomes congested, which minimizes the performance of the system. Therefore, to develop a dependable SMS system, we need a reliable verification method. Besides the agent-based verification method, formal method verification on the design is also needed. This is to ensure that the system design is secured from the unseen errors and bugs in the early stage of development. In order to make this successful, this paper will discuss more on the verification design of short-text messaging system with the implementation of an agent-based system known as model checking. The aim of this paper is to provide a reliable and verifiable system designs, using Spin as the model checker.